Efektivitas penerapan pembayaran online berbasis e-Samsat dalam penerimaan pajak kendaraan bermotor pada Badan Pendapatan Daerah Provinsi Sulawesi Utara - Opit, Ananda Nikita; Budiarso, Novi Swandari; Tangkuman, Steven (Riset Akuntansi dan Manajemen Pragmatis, 2024)
In the current era where everything can be done using technology, including paying vehicle tax, the E-Samsat online application is expected to increase Regional Original Income in North Sulawesi Province. Therefore, I want to know the effectiveness of implementing E-Samsat in the community environment in the Regional Revenue Agency of North Sulawesi Province. This type of research is descriptive qualitative. The results of the research show that there is an increase in the target and realization of Motor Vehicle Tax revenue in 2020-2022, but it decreases in 2023. Judging from the data on Motor Vehicle Tax revenue through the E-Samsat based online application in 2020-2022 there is also an increase, and the same Just as target and realization data will decline in 2023, revenue via E-Samsat will also experience a decline in the number of people paying vehicle tax. However, according to the effectiveness ratio criteria determined by the Ministry of Home Affairs through Minister of Home Affairs Decree No. 690,900,327 concerning Guidelines for Financial Performance Assessment, the total amount of target data and realization of Motor Vehicle Tax revenue is included in the effective category. One of the factors that has not achieved the target and realization of Motor Vehicle Tax revenue is the lack of equitable outreach to all regions. Therefore, the Government, through the Regional Revenue Agency of North Sulawesi Province, must provide more extensive outreach or outreach to the community directly.